ETHANOL EXTRACT OF Moringa oleifera INCREASED THE NUMBER OF SPERMATOZOA AND IMPROVED SPERM MORPHOLOGY OF OLD Rattus norvegicus - Luh Putu Widiastini; I Gusti Agung Manik Karuniadi; Made Tangkas (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2022)
Aging in men can lead to decreased semen volume, abnormal sperm morphology, and decreased sperm motility. This study aims to determine the effect of ethanol extract of moringa (Moringa oleifera) leaf on the number and morphology of spermatozoa in old Wistar rats (Rattus norvegicus). This study used healthy old rats, 18–19 months old, with a bodyweight of 200–250 g and no physical disabilities. The 36 rats were divided into 2 groups, i.e. the treatment group (fed with ethanol extract of moringa leaves 50 mg/kgBW/0.5 mL CMC 0.5% every day) and the control group (0.5 mL CMC 0.5% every day) for 30 days. The results showed that moringa leaf ethanol extract increased the number of spermatozoa (p-value 0.000) and improved spermatozoa morphology (p-value 0.000). It can be concluded that the ethanol extract of moringa leaves significantly increased the number and improved the morphology of the spermatozoa in the aged rats.  Penuaan pada pria dapat menyebabkan penurunan volume semen, morfologi yang abnormal dan penurunan motilitas sperma. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh pemberian ekstrak etanol daun kelor (Moringa oleifera) terhadap jumlah serta morfologi spermatozoa tikus putih (Rattus norvegicus) galur Wistar usia tua. Penelitian ini menggunakan tikus tua yang berusia 18–19 bulan dengan berat badan 200–250 g, kondisi sehat dan tidak cacat fisik. Sebanyak 36 ekor tikus dibagi menjadi 2 kelompok, yaitu kelompok perlakuan (ekstrak etanol daun kelor 50 mg/kgBB/0,5 mL CMC 0,5% per hari) dan kelompok kontrol (CMC 0,5% 0,5 mL per hari) selama 30 hari. Hasil penelitian menunjukkan bahwa ekstrak etanol daun kelor meningkatkan jumlah spermatozoa (nilai p 0,000) dan memperbaiki morfologi spermatozoa (nilai p 0,000). Dapat disimpulkan bahwa pemberian ekstrak etanol daun kelor secara signifikan meningkatkan jumlah dan kualitas morfologi spermatozoa tikus putih usia tua.